STUDENTS' PERCEPTIONS ON THE USE OF ELSA SPEAK APPLICATION TO IMPROVE ENGLISH SPEAKING SKILLS - Yuliawati, Neng Lies; Suryadi, Suryadi (TELL - US JOURNAL, 2023)
Students encounter various challenges when striving to enhance their English-speaking abilities, one of which is the lack of sufficient learning tools, which might impede the progress of these talents. It's possible that some pupils won't have enough time to focus on their English skill. In the modern era, there exists a multitude of technologies and programs that might enhance one's English speaking proficiency. Among these options is the utilization of the ELSA Speak application. The goal of this study is to investigate students' viewpoints regarding the effectiveness of the ELSA Speak application in improving their English speaking skills. The study aims to evaluate students' perspectives regarding the efficacy of ELSA Speak as a means of enhancing their English speaking abilities. Additionally, it aims to investigate the extent to which students believe that the utilization of ELSA Speak can yield beneficial outcomes. A positive perspective on their proficiency in English communication, as well as factors that could influence their opinion of the application. This study employed simple random sampling methodology, wherein a sample of 60 individuals was chosen from a population of 100. Utilizing a survey instrument to gather information. The data was subjected to statistical analysis using SPSS 16.0, which involved calculating the mean correlation and average. Quantitative descriptive analysis employing Pearson correlation and Cronbach's alpha. The results of the questionnaire validation indicate that each statement item has passed due to the fact that the rcount value is greater than the rtable value. The Cronbach's alpha test yielded a high value of 0.955, indicating a strong level of reliability for the instrument. The study's findings suggest that the participants had a positive view on improving English speaking abilities using the ELSA speak application as a learning tool. In addition, pupils expressed positive experiences with the application. The users highlighted the user-friendly design, extensive range of materials, and significant improvement in their oral communication skills with frequent use of ELSA Speak. The research supports the use of this program as an effective tool for improving English speaking skills